Family Communication Patterns In The Era Digital Technology - Anisti Anisti; Resman Muharul Tambunan; Veranus Sidharta; Sampean Sampean; Syatir Syatir (ARRUS Journal of Social Sciences and Humanities, 2023)
Communication dynamics in the family environment have a major impact on the relationships between family members and their psychosocial development. However, with the rapid progress of information and communication technology, especially in the current digital era, there have been quite striking changes in family communication patterns. Ease of access to digital devices and communication platforms can make many people feel obliged to stay connected, checking messages, email or social media constantly. Therefore, family members need to learn to manage their time wisely so that direct interactions and family activities remain a priority. This research was conducted in Bahagia Pondok Ungu Permai Village, Bekasi City. The method of qualitative descriptive research and interviews was conducted with two married couples, residents of Pondok Ungu Permai. The results of this research show that digital technology can have a positive impact on family communication, facilitating long-distance interactions, enabling quick sharing of information, and helping to monitor children.